Asphalt mixture modifier and preparation method thereof
By using mixed fibers, ultraviolet radiation modified polyester fibers, silane coupling agents and graphene components in the asphalt mixture, a stable three-dimensional network structure is formed, which solves the problems of poor high-temperature stability and low-temperature crack resistance asphalt pavement, and achieves significant performance improvement and cost reduction.
Patent Information
- Application Number
- CN202411786521.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The existing asphalt pavement has poor stability at high temperatures and poor crack resistance at low temperatures, making it difficult to improve high temperature stability and low temperature crack resistance at both.
The asphalt mixture modifier including mixed fibers, ultraviolet radiation modified polyester fibers, silane coupling agents and graphene is used to improve the high-temperature stability and low-temperature crack resistance of the asphalt mixture by forming a stable three-dimensional network structure and improving the stability and elongation of the break.
It significantly improves the high-temperature stability and low-temperature crack resistance of asphalt mixture, extends the service life, and reduces construction costs and equipment requirements.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of asphalt additives, and in particular to an asphalt mixture modifier and a preparation method thereof. Background Art
[0002] Asphalt pavement refers to various types of pavement paved with asphalt materials mixed into mineral materials, which has many advantages. The asphalt pavement has a smooth surface and good driving comfort, and has good wear resistance and durability, and can withstand a large amount of traffic load and erosion from the natural environment. However, the long-term use of asphalt pavement will be repeatedly affected by vehicle loads, especially in low temperature environments, and the pavement is prone to cracks. In hot seasons, asphalt pavements are prone to high-temperature deformation. Therefore, improving the high temperature resistance and low-temperature cracking resistance of asphalt pavement is an urgent problem to be solved.
[0003] There are many ways to improve the high temperature resistance and low temperature cracking resistance of asphalt pavement, including: adding polymers to improve the performance of asphalt, but there are problems of high cost and complex process, and it is impossible to improve high temperature stability and low temperature cracking resistance at the same time; there is also a method of improving asphalt performance by adjusting the production process of asphalt mixture, but this method has high requirements for equipment and process, and is time-consuming and labor-intensive; there is also a method of increasing the thickness of the asphalt surface layer to improve the low temperature cracking resistance, but this will increase construction costs and time, and may also have a certain impact on the pavement structure. Based on the defects of the above-mentioned improvement methods, it is urgent to provide an asphalt mixture modifier and its preparation method to solve the problem of poor high temperature stability and low temperature cracking resistance of existing asphalt pavements. Summary of the invention
[0004] In view of the problems that the existing asphalt mixture modifier has poor high temperature stability and poor low temperature crack resistance, the present invention provides an asphalt mixture modifier and a preparation method thereof.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] The first aspect of the present invention provides an asphalt mixture modifier, comprising the following components in parts by weight: 35-40 parts of mixed fiber, 13-16 parts of silane coupling agent and 4-7 parts of graphene;
[0007] The mixed fiber is a mixture of cotton fiber and modified polyester fiber;
[0008] The modified polyester fiber is ultraviolet irradiated polyester fiber.
[0009] Compared with the prior art, the main component of the asphalt mixture modifier provided by the present invention is mixed fiber. The modified polyester fiber of the mixed fiber is a polyester fiber modified by ultraviolet irradiation. Ultraviolet irradiation can cause chemical changes on the surface of the polyester fiber, causing the chemical bonds on the fiber surface to break and reorganize, thereby promoting the polyester fiber to form a more stable chemical structure, thereby improving the stability and durability of the polyester fiber, thereby improving the service life of the asphalt mixture; and ultraviolet radiation can also increase the elongation at break of the polyester fiber to a certain extent. Applying it to the asphalt mixture modifier can significantly improve the anti-cracking performance of asphalt; the modified polyester fiber can also alleviate the softening speed of asphalt by absorbing part of the heat of the asphalt mixture, thereby improving the high-temperature stability; the surfaces of cotton fiber and modified polyester fiber have more active groups, and the silane coupling agent can connect the cotton fiber and the modified polyester fiber together to form a stable three-dimensional network structure. Applying it to the asphalt mixture can absorb and disperse part of the stress, reducing the stress inside the asphalt mixture. The cotton fibers and modified polyester fibers can be concentrated to delay the formation of cracks and improve the anti-cracking performance of the asphalt mixture. The stable three-dimensional network structure formed by the cotton fibers and the modified polyester fibers can also effectively restrict the flow of the asphalt mixture under high temperature conditions, thereby improving the high-temperature stability of the asphalt mixture. The polyester fibers after ultraviolet irradiation have a certain degree of roughness and the cotton fiber surface has depressions. When the two fibers are used at the same time, a synergistic effect is produced, which greatly increases the bonding area and bonding strength between the asphalt mixture modifier and the asphalt mixture, and significantly improves the anti-cracking performance of the asphalt by increasing the interaction force between the asphalt, aggregate and the asphalt mixture modifier in the asphalt mixture. The composite fibers formed by the cotton fibers and the modified polyester fibers are prone to agglomeration. The present invention adds graphene as a dispersant for the asphalt mixture modifier, so that the composite fibers formed by the cotton fibers and the modified polyester fibers can be evenly dispersed in the asphalt mixture, further improving the anti-cracking performance of the asphalt mixture, and the graphene can also fill the voids in the asphalt mixture, thereby inhibiting the expansion of cracks.
[0010] Preferably, the mass ratio of cotton fiber to modified polyester fiber in the mixed fiber is 1:(1.4-1.6).
[0011] The preferred ratio of cotton fiber to modified polyester fiber can form a three-dimensional network structure and give it a certain force-bearing capacity, thereby improving the anti-cracking performance of the asphalt mixture.
[0012] Preferably, the ultraviolet intensity of the ultraviolet irradiation is 30 μW / cm 2 -35μW / cm 2 .
[0013] The irradiation time of the ultraviolet irradiation is 10min-12min.
[0014] By controlling the time of ultraviolet irradiation, a specific content of active groups can be formed on the surface of polyester fibers, which is beneficial to increasing the subsequent cross-linking density with silane coupling agents; specific ultraviolet irradiation conditions can also enable polyester fibers to form a more stable chemical structure, thereby improving the anti-cracking performance of asphalt mixtures by increasing the service life of asphalt mixtures.
[0015] Preferably, the silane coupling agent is a mixture of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane.
[0016] Further preferably, the mass ratio of γ-(methacryloyloxy)propyltrimethoxysilane to vinyltriethoxysilane in the silane coupling agent is 1:(0.9-1.2).
[0017] The present invention selects a specific silane coupling agent to further improve the crosslinking density between the silane coupling agent and the cotton fiber and the modified polyester fiber, so that the cotton fiber and the modified polyester fiber form a stable three-dimensional network structure, thereby improving the anti-cracking performance of the asphalt mixture.
[0018] The present invention also provides a method for preparing the above-mentioned asphalt mixture modifier, comprising the following steps:
[0019] S1, adding the silane coupling agent into an ethanol aqueous solution to obtain a mixed solution;
[0020] S2, adding the mixed fiber to the mixed solution, reacting at 85° C.-88° C. to obtain a first reaction solution;
[0021] S3. Add the graphene to the first reaction liquid, keep warm at 110° C.-120° C., filter, wash, and dry to obtain the asphalt mixture modifier.
[0022] Further preferably, in S1, the mass concentration of the ethanol aqueous solution is 15%-20%.
[0023] Further preferably, in S1, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:(14-16).
[0024] Further preferably, in S2, the reaction time is 60-70 min.
[0025] Further preferably, in S3, the insulation time is 2.5h-3h.
[0026] The asphalt mixture modifier provided by the present invention has a simple preparation process, low equipment requirements and low production cost, can be directly thrown in for stirring, and is applied to asphalt mixtures to significantly improve the service life and crack resistance of asphalt mixtures. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] Example 1
[0029] The present embodiment provides an asphalt mixture modifier, comprising the following components in parts by weight: 35 parts of mixed fiber, 13 parts of silane coupling agent, and 7 parts of graphene; wherein the mixed fiber is a mixture of cotton fiber and modified polyester fiber in a mass ratio of 1:1.5, and the modified polyester fiber is modified by ultraviolet irradiation, and the ultraviolet intensity of the ultraviolet irradiation is 30 μW / cm 2 , the irradiation time is 10 min, and the silane coupling agent is a mixture of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 1:1;
[0030] The preparation method of the asphalt mixture modifier comprises the following steps:
[0031] S1, adding the silane coupling agent to an ethanol aqueous solution with a mass concentration of 15% to obtain a mixed solution; wherein the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:15;
[0032] S2, adding the mixed fiber to the mixed solution, reacting at 85° C. for 60 min to obtain a first reaction solution;
[0033] S3. Add the graphene to the first reaction liquid, keep it warm at 120° C. for 3 hours, filter, wash, and dry to obtain the asphalt mixture modifier.
[0034] Example 2
[0035] The present embodiment provides an asphalt mixture modifier, comprising the following components in parts by weight: 40 parts of mixed fiber, 16 parts of silane coupling agent, and 4 parts of graphene; wherein the mixed fiber is a mixture of cotton fiber and modified polyester fiber in a mass ratio of 1:1.4, and the modified polyester fiber is modified by ultraviolet irradiation, and the ultraviolet intensity of the ultraviolet irradiation is 35 μW / cm 2 , the irradiation time is 12 min, and the silane coupling agent is a mixture of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 1:0.9;
[0036] The preparation method of the asphalt mixture modifier comprises the following steps:
[0037] S1, adding the silane coupling agent to an ethanol aqueous solution with a mass concentration of 20% to obtain a mixed solution; wherein the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:14;
[0038] S2, adding the mixed fiber to the mixed solution, reacting at 88° C. for 70 min to obtain a first reaction solution;
[0039] S3. Add the graphene to the first reaction liquid, keep it warm at 110° C. for 2.5 hours, filter, wash, and dry to obtain the asphalt mixture modifier.
[0040] Example 3
[0041] The present embodiment provides an asphalt mixture modifier, comprising the following components in parts by weight: 38 parts of mixed fiber, 14 parts of silane coupling agent, and 6 parts of graphene; wherein the mixed fiber is a mixture of cotton fiber and modified polyester fiber in a mass ratio of 1:1.6, and the modified polyester fiber is modified by ultraviolet irradiation, and the ultraviolet intensity of the ultraviolet irradiation is 33 μW / cm 2 , the irradiation time is 11 min, and the silane coupling agent is a mixture of γ-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane in a mass ratio of 1:1.2;
[0042] The preparation method of the asphalt mixture modifier comprises the following steps:
[0043] S1, adding the silane coupling agent to an ethanol aqueous solution with a mass concentration of 18% to obtain a mixed solution; wherein the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:16;
[0044] S2, adding the mixed fiber to the mixed solution, reacting at 86° C. for 65 min to obtain a first reaction solution;
[0045] S3. Add the graphene to the first reaction liquid, keep it warm at 113° C. for 2.8 hours, filter, wash, and dry to obtain the asphalt mixture modifier.
[0046] Example 4
[0047] This embodiment provides an asphalt mixture modifier, which is different from Embodiment 1 in that:
[0048] The vinyltriethoxysilane in Example 1 was replaced with an equal amount of γ-(methacryloyloxy)propyltrimethoxysilane;
[0049] The other ingredients and steps are the same as those in Example 1.
[0050] Comparative Example 1
[0051] This comparative example provides an asphalt mixture modifier, which is different from Example 1 in that:
[0052] The graphene in Example 1 is replaced by an equal amount of silicon dioxide nanosheets;
[0053] The other ingredients and steps are the same as those in Example 1.
[0054] Comparative Example 2
[0055] This comparative example provides an asphalt mixture modifier, which is different from Example 1 in that:
[0056] The cotton fiber in Example 1 is replaced with an equal amount of viscose fiber;
[0057] The other ingredients and steps are the same as those in Example 1.
[0058] Comparative Example 3
[0059] This comparative example provides an asphalt mixture modifier, which is different from Example 1 in that:
[0060] The polyester fiber in Example 1 is replaced with an equal amount of cotton fiber;
[0061] The other ingredients and steps are the same as those in Example 1.
[0062] The asphalt mixture modifiers prepared in Examples 1-4 and Comparative Examples 1-3 were added to the asphalt mixture at a weight ratio of 0.35:100; wherein the asphalt mixture gradation was AC13, the asphalt type was 70# base asphalt, the aggregate type was limestone, and the oil-stone ratio was 5.0%. The following performance tests were performed according to the test method in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures for Highway Engineering":
[0063] High temperature rutting resistance test: add asphalt mixture modifier to asphalt mixture, and test the rutting dynamic stability of asphalt mixture; during the test, the temperature is 60℃ and the wheel pressure is 0.7MPa;
[0064] Low temperature crack resistance test: The asphalt mixture modifier was added to the asphalt mixture, and the splitting tensile strength test of the asphalt mixture was carried out; wherein, during the test, the temperature was -10°C; the test results are shown in Table 1:
[0065] Table 1
[0066] Test items Rutting dynamic stability (times / mm) Splitting tensile strength (MPa) Example 1 6414 6.8 Example 2 6262 6.6 Example 3 6117 6.5 Example 4 6360 5.9 Comparative Example 1 6210 3.1 Comparative Example 2 4920 4.0 Comparative Example 3 4730 3.6
[0067] The asphalt mixture modifier provided in the embodiment of the present invention, which is prepared by adding cotton fiber, ultraviolet radiation modified polyester fiber, silane coupling agent and graphene, is applied to asphalt, which can significantly improve the high temperature stability and low temperature cracking resistance of the asphalt mixture modifier; while the asphalt mixture modifiers prepared in comparative examples 1-3, whether replaced with other fibers or using silica nanosheets, cannot achieve the effect achieved in the embodiment of the present application.
[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An asphalt mixture modifier, characterized in that: The invention comprises the following components in parts by weight: 35-40 parts of mixed fiber, 13-16 parts of silane coupling agent and 4-7 parts of graphene; The mixed fiber is a mixture of cotton fiber and modified polyester fiber; The modified polyester fiber is ultraviolet irradiated polyester fiber.
2. The asphalt mixture modifier according to claim 1, characterized in that: The mass ratio of cotton fiber to modified polyester fiber in the mixed fiber is 1:(1.4-1.6).
3. The asphalt mixture modifier according to claim 1, characterized in that: The ultraviolet intensity of the ultraviolet irradiation is 30 μW / cm 2 -35μW / cm 2 .
4. The asphalt mixture modifier according to claim 1 or 3, characterized in that: The irradiation time of the ultraviolet irradiation is 10min-12min.
5. The asphalt mixture modifier according to claim 1, characterized in that: The silane coupling agent is a mixture of gamma-(methacryloyloxy)propyltrimethoxysilane and vinyltriethoxysilane.
6. The asphalt mixture modifier according to claim 5, characterized in that: The mass ratio of γ-(methacryloyloxy)propyltrimethoxysilane to vinyltriethoxysilane in the silane coupling agent is 1:(0.9-1.2).
7. A method for preparing the asphalt mixture modifier according to any one of claims 1 to 6, characterized in that: The steps include: S1, adding the silane coupling agent into an ethanol aqueous solution to obtain a mixed solution; S2, adding the mixed fiber to the mixed solution, reacting at 85° C.-88° C. to obtain a first reaction solution; S3. Add the graphene to the first reaction liquid, keep warm at 110° C.-120° C., filter, wash, and dry to obtain an asphalt mixture modifier.
8. The method for preparing an asphalt mixture modifier according to claim 7, characterized in that: In S1, the mass ratio of the silane coupling agent to the ethanol aqueous solution is 1:(14-16); and / or In S1, the mass concentration of the ethanol aqueous solution is 15%-20%.
9. The method for preparing an asphalt mixture modifier according to claim 7, characterized in that: In S2, the reaction time is 60-70 min.
10. The method for preparing an asphalt mixture modifier according to claim 7, characterized in that: In S3, the insulation time is 2.5h-3h.
Citation Information
Patent Citations
Multifunctional composite fiber anti-cracking material and preparation method thereof
CN103449747A
Modified regenerated polymer fiber, asphalt mixture containing fiber and preparation method thereof
CN111188182A
Low-grade modified asphalt suitable for rigid-flexible composite long-life pavement and preparation method of low-grade modified asphalt
CN112538274A
Environment-friendly odorless asphalt mixture and preparation method thereof
CN114573283A
Cement-based grouting material containing composite fibers and preparation method
CN118754539A
Cited By
Fiber reinforced asphalt mixture and preparation method thereof
CN120829269A
Fiber reinforced asphalt mixture and method of making same
CN120829269B